'Helena Blavatsky, Dorothy Field and Annie Besant: Theosophy's role in introducing Sikhism to the West'. (2nd July 2020) - Nesbitt, Eleanor
ABSTRACT: The Theosophical Society, founded in 1875 as a universal brotherhood without distinction of race, creed, colour, gender or social background, promoted an 'ageless wisdom' that resonates to some extent with Sikh teachings. This article explores how Theosophists and Theosophy introduced Sikhism to a western audience, by focusing on Helena Blavatsky, Annie Besant and Dorothy Field. The three women's political and religious views coloured their representation of Sikhs and Sikhism. Excerpts exemplify the women's attention to Guru Nanak and subsequent Gurus – notably Guru Gobind Singh and Sikh history and their distinctive styles and focus.